PERANCANGAN ALAT PENGANGKUT KOMPONEN SPOOL WIRE DI PT KEMET ELECTRONICS INDONESIA - Siburian, Marben; Sirait, Ganda (LPPM Universitas Putera Batam, 2021)
PT Kemet Electronics Indonesia is an international company that produces film capacitor products. An international company is certainly very concerned about the aspects of continuous improvement in its business. One of the jobs that requires repairs to the saction assembly. Where there is work to lift materials weighing up to 85 kg. This work can cause injury to workers if done manually. For this reason, it is necessary to have a problem-solving solution to the current material handling conditions. Axiomatic design is a design methodology that can produce complex design solutions in a systematic and scalable manner. House Of Quality is a tool that can be used to translate customer needs into product specifications so that products can properly satisfy customer needs. Axiomatic House Of Quality (AHOQ) is a combination of the two methods that can be used to produce good designs in a systematic and at the same time measuring design solutions based on customer needs. The research resulted in three functions, each of which is a function domain in each of the physical solution domains. The areas of this function are lifting the overflowing material with a hydraulic system, moving the backed material using the wheel system, and maintaining the quality of the material filled with the clamping arm system. The functional and physical domains are poured into a tool for transporting the coil wire material. With this tool, the work of lifting materials weighing 85 kg is no longer done by humans so that the work safety of employees can be improved.